An exploratory study of the integration of fuel cell systems inside Hcl/naoh plants for industrial hydrogen use - Fernandes Braga, José Mauro; Seidl, Peter (Revista Ciências Exatas, 2009)
This work aims to demonstrate the economic viability of the application of industrial hydrogen in fuel cell systems by analysing the advantages and disadvantages of this investment in HCl/NaOH plants. Using the Present Liquid Value and the Real Options Theory an economic avaliation will be made of the integration of fuel cell system in these plants, based on investment cost, volatility, among other parameters